Phylogenetic status of some unique species representing Blapstinina Mulsant & Rey (Tenebrionidae: Blaptinae: Opatrini), and implications for continued study of the subtribe - Kamiński, Marcin Jan; Lumen, Ryan; Kanda, Kojun; Smith, Aaron Dennis (Zootaxa, 2022)
Blapstinus Dejean is the most taxonomically challenging genus within Blapstinina Mulsant & Rey (Tenebrionidae: Opatrini). With over 120 species, it is widely distributed throughout the Americas, with representatives reaching Canada on the northern range edge, and Argentina, Chile, and Uruguay in the south. Traditionally, Blapstinus has been distinguished from other blapstinoid beetles via well-developed metathoracic wings and their lack of synapomorphies present in other genera; however, fused and tapering aedeagal parameres were recently introduced as a potential autapomorphy for the genus. This study used molecular data (nuclear ribosomal 28S, cytochrome oxidase subunit II (COII), arginine kinase (ArgK), carbomyl-phosphate synthetase domain of rudimentary (CAD), and wingless (wg)) to investigate the phylogenetic placement and taxonomic status of three Blapstinus species with distinct male genitalic morphology, i.e. Blapstinus tibialis Champion (USA), B. grandis Champion (Mexico, Nicaragua), and B. punctulatus Solier (Argentina, Bolivia, Brazil, Chile, Uruguay). Analyses highlight the phylogenetic informativeness of the aedeagal morphology within the subtribe, and support an urgent need for taxonomic studies of South American taxa. Blapstinus tibialis and B. grandis were recovered as a specific lineage within Blapstinus that can be easily distinguished from remaining congeners by having tridentate parameres. A lectotype for B. grandis is designated to fix the taxonomic status of this species. Blapstinus punctulatus was recovered outside of its current genus which, along with aedeagal morphology, supports a change of status of the species. As a result, the following synonymy and combinations are introduced: Lodinus Mulsant and Rey stat. restit. (=Austrocaribius Marcuzzi syn. nov.), Lodinus araguae (Marcuzzi) comb. et stat. nov., L. punctulatus comb. nov., L. venezuelensis (Marcuzzi) comb. nov. Lectotypes for Lodinus nigroaeneus Mulsant and Rey, L. araguae, and L. punctulatus are designated to fix the taxonomic status of these species.